2002
DOI: 10.1590/s1516-35982002000100011
|View full text |Cite
|
Sign up to set email alerts
|

Exigência de Lisina para Machos Castrados de Dois Grupos Genéticos de Suínos na Fase de Terminação, com Base no Conceito de Proteína Ideal

Abstract: Foi conduzido um experimento para determinar as exigências de lisina de machos castrados, em fase de terminação, de dois grupos genéticos de suínos, com base no conceito de proteína ideal. Foram utilizados 16 suínos do grupo genético comum (GGC) e 16 suínos do grupo genético melhorado (GGM), distribuídos em quatro tratamentos que consistiram de uma ração basal, à base de milho e farelo de soja, contendo 0,60% de lisina e outras três rações, acrescentando-se níveis crescentes de lisina para se obter 0,75, 0,90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
11

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
2
5
0
11
Order By: Relevance
“…(2007), the inconsistency of the results found in studies examining the effects of increasing levels of dietary lysine on carcass traits of pigs may be related, among other factors, to the genotypic differences concerning meat deposition potential. This is in agreement with the results found by Gasparotto et al (2001) and Moreira et al (2002), who evaluated the lysine requirement of barrows from two genetic groups (common and improved) from 24 to 50 kg and 50 to 90 kg, respectively. They found that the levels of lysine influenced loin-eye area and depth, which varied between the genetic groups.…”
Section: Ingredientsupporting
confidence: 93%
“…(2007), the inconsistency of the results found in studies examining the effects of increasing levels of dietary lysine on carcass traits of pigs may be related, among other factors, to the genotypic differences concerning meat deposition potential. This is in agreement with the results found by Gasparotto et al (2001) and Moreira et al (2002), who evaluated the lysine requirement of barrows from two genetic groups (common and improved) from 24 to 50 kg and 50 to 90 kg, respectively. They found that the levels of lysine influenced loin-eye area and depth, which varied between the genetic groups.…”
Section: Ingredientsupporting
confidence: 93%
“…PUN generally shows a high variance (Coma et al, 1995) and in some studies, PUN was not efficient to determine the lysine requirement (Fontes et al,.1999;Gasparotto et al, 2001;Hannas et al, 2000;Moreira et al, 2002. In this trial, the CCGG showed greater values of standard deviation for PUN than DLGG (Table 2).…”
Section: Resultsmentioning
confidence: 60%
“…Similarly, for the variable feed, Moreira et al (2002) also found no effect of lysine level on feed intake. Contrasting with the results observed in this study, several authors (Cline et al 2000;Fabian et al, 2001) found a positive effect of lysine levels on the efficiency of feed utilization for weight gain in pigs in the finishing phase with final weights above 100 kg.…”
Section: Resultsmentioning
confidence: 78%